Bulgarian experience on the legal regulation of examples and types of cases in administrative judiciary - Nikolayets, V. (Київський національний університет імені Тараса Шевченка, 2019)
In the article the specifics of Bulgaria's experience in the legal regulation of model and typical cases in administrative proceedings are analyzed. The peculiarities of administrative and legal regulation of the specified sphere are revealed. Proposals for borrowing from the national legislation the positive experience of Bulgaria on the legal regulation of model and typical cases in administrative justice are formulated.

У статті проаналізовано специфіку досвіду Болгарії щодо правового регулювання зразкових та типових справ в адміністративному судочинстві. Виявлено особливості адміністративно-правового регулювання вказаної сфери. Сформульовано пропозиції щодо запозичення у національне законодавство позитивного досвіду Болгарії щодо правового регулювання зразкових та типових справ в адміністративному судочинстві.
Болгарський досвід щодо правового регулювання зразкових та типових справ в адміністративному судочинстві
Keywords: model cases; standard cases; administrative justice; administrative legislation; Bulgaria.; зразкові справи; типові справи; адміністративне судочинство; адміністративне законодавство; Болгарія.